The Position of The Applicative Model in The Formation of Complex Syntactic Structures - Rustam Dusyorovich Samandarov (Scientific Trends, 2023)
In this article, some comments were made on the derivational properties of complex syntactic structures and the role of the applicative model in their formation. Theoretical considerations are also given about the position of operators in the derivation of complex syntactic structures and, consequently, about the position of applicators.
Keywords: applicator, derivation, complex syntactic structures, operand, derivative.